Factors Affecting Students’ Satisfaction Towards Bus Services in Campus/Masnita Misiran...[et al.] - Sapiri, Hasimah; Md Yusof, Zahayu; Mahmuddin, Massudi; Misiran, Masnita (Universiti Teknologi MARA Cawangan Sarawak, 2021)
The reliability of public transport services (e.g., bus) is a critical factor to be considered among public transport users. This factor is important for the consequences that come with unreliability will significantly increase unnecessary anxiety and discomfort. Such consequences include additional waiting time, late arrival at destinations, and missed connections. The ability of the system to follow the planned schedule and maintain consistent travel time are some of the factors that need to be in focus. In this study, we investigated satisfaction among students who reside in campus towards bus services provided by the university. Factor analysis and structural models were developed to achieve the research objective. Three factors have significant relationships with students’ satisfaction. The finding also indicated that bus services are an important requirement of the on-campus students.